2022
DOI: 10.3389/fphar.2022.875103
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism Underlying Acupuncture Therapy in Spinal Cord Injury: A Narrative Overview of Preclinical Studies

Abstract: Spinal cord injury (SCI) results from various pathogenic factors that destroy the normal structure and function of the spinal cord, subsequently causing sensory, motor, and autonomic nerve dysfunction. SCI is one of the most common causes of disability and death globally. It leads to severe physical and mental injury to patients and causes a substantial economic burden on families and the society. The pathological changes and underlying mechanisms within SCI involve oxidative stress, apoptosis, inflammation, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 174 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…There is a growing incidence in clinical settings of SCI, a serious disorder of the central nervous system. For the treatment and rehabilitation of SCI, TCM has been widely used, [ 32 ] including acupuncture, [ 33 ] moxibustion, [ 34 ] and Chinese herbal medicine. [ 35 ] Mechanisms of TCM for SCI involve the inhibition of inflammation, [ 36 ] lipid peroxidation, [ 37 ] neuronal cell death, [ 38 ] improvement of microcirculation, [ 39 ] and promotion of axonal regeneration, [ 40 ] with interactions and interrelations between multiple molecular mechanisms that promote functional recovery after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing incidence in clinical settings of SCI, a serious disorder of the central nervous system. For the treatment and rehabilitation of SCI, TCM has been widely used, [ 32 ] including acupuncture, [ 33 ] moxibustion, [ 34 ] and Chinese herbal medicine. [ 35 ] Mechanisms of TCM for SCI involve the inhibition of inflammation, [ 36 ] lipid peroxidation, [ 37 ] neuronal cell death, [ 38 ] improvement of microcirculation, [ 39 ] and promotion of axonal regeneration, [ 40 ] with interactions and interrelations between multiple molecular mechanisms that promote functional recovery after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no reports of severe adverse events following electroacupuncture therapy were noted, but medium‐level adverse events, such as dizziness and gastrointestinal disorders, and slight side effects, such as hematoma and nausea, could occur (Xiong et al, 2019). With the domestic and international application of acupuncture therapy in clinical practice, a growing number of scientists expect acupuncture therapy to inspire new ideas for SCI treatment (Jiang et al, 2022). Researchers have been studying the mechanism underlying the neural recovery promoted by EA for many years.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that astrocyte activation is a crucial factor in neuroinflammation, which in turn leads to neuronal damage 42 . Recent research has revealed that reactive astrocytes can harm the nervous system by releasing toxins such as TNF‐α, IL‐1β, IL‐6, and saturated lipids, leading to synaptic abnormalities and neuronal death 43 . However, some research has indicated that type 2 astrocytes (A2) can protect neurons by releasing neurotrophic factors, such as BDNF.…”
Section: Discussionmentioning
confidence: 99%
“… 42 Recent research has revealed that reactive astrocytes can harm the nervous system by releasing toxins such as TNF‐α, IL‐1β, IL‐6, and saturated lipids, leading to synaptic abnormalities and neuronal death. 43 However, some research has indicated that type 2 astrocytes (A2) can protect neurons by releasing neurotrophic factors, such as BDNF. Our study shows that CS exposure is associated with substantial neuronal death and neuroinflammation in the CA1 region of the hippocampus, highlighted by the upregulation of pro‐apoptotic markers such as TUNEL and BAX.…”
Section: Discussionmentioning
confidence: 99%